CORRELATION BETWEEN IMMUNIZATION STATUS AND MOTHER’S HEIGHT, AND STUNTING IN CHILDREN 2–5 YEARS IN INDONESIA - Risna Nur Fajariyah; Atik Choirul Hidajah (Universitas Airlangga, 2020)
Background: Stunting is a condition where the growth and development of a child fails during the first 1,000 days of life. The number of stunted children in Indonesia has increased from 35.60% in 2010 to 37.20% in 2013. Purpose: The aim of this study is to analyse the relationship between immunisation status and stunting in children 2–5 years. Methods: This is a secondary data analysis with cross-sectional study design. The data used for this study were obtained from Indonesia Family Live Survey wave 5 (IFLS-5). IFLS-5 was conducted in 13 provinces from October 2014 until April 2015. The data were collected from 1,048 respondents aged 2–5 years in the IFLS-5 with completed age and height data. The observed variables were age, sex, immunisation status, history of infection, mother’s height, mother’s age during pregnancy, living area, and region. Results: This research shows that there is a relationship between immunisation status (p = 0.01; OR =1.78; 95% CI = 1.26 < OR < 2.52), mother’s height (p = 0.00; OR = 1.41; 95% CI = 1.00 < OR < 1.98) and stunting in children aged 2–5 years. Conclusion: Immunisation status and mother’s height are associated with stunting in children aged 2–5 years.